Effects of physical exercise on butyrylcholinesterase in obese adolescents - Silva, Isabela M.W. (Sociedade Brasileira de Genética, 2012)
The aim of the present study was to evaluate the effect of a 12 week program of physical exercise (PE) on butyrylcholinesterase (BChE) in obese adolescents. This study compared obese adolescents (N = 54) before and after PE, regarding the relative intensity (RI) and activity of different molecular forms (G1, G2, G4 and G1-ALB) of BChE found in plasma. Waist circumference (WC) and lipid profile were also assessed before and after PE. It was shown that before PE, mean plasma BChE activity was significantly higher in obese than in non-obese adolescents and that it was significantly reduced after PE, becoming similar to that found in non-obese adolescents. Lipid profile and WC also changed in response to PE. These results are consistent with studies that found a correlation between BChE and lipid metabolism and suggest that PE may have led to a physiological regularization of plasma BChE activity. Although mean BChE activity of each isoform was significantly reduced by PE, their RI did not change. This is in accordance with a previous suggestion that this proportion is maintained under factors such as obesity, and may therefore be important for BChE functions.